PENGEMBANGAN MODEL TAFSIR PENDIDIKAN PERFEKTIF ‘ALÎ ‘ABD AL-ḤALÎM MAḤMÛD - Arif, Mahmud (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This paper deals with the idea of ?Alî ?Abd al-?alîm Ma?mûd, who has seriousely built a firm conviction on the perfection of the Qur?an and the necessity of Moslems to obey it. The only way to solve any problem in this life, according to him, is by returning to the guidance of the Qur?an and the Prophet traditions. ?Abd al-?alîm Ma?mûd has utilized two models in elaborating the Qur?anic tenets, i.e.: [1] selecting a certain surah to be interpreted; and [2] appointing a certain educational topic and explaining the relevant content of Qur?anic verses. Those models stand on assumption that the Qur?an, as a guidance book, has explained all matters of human life. His belief in an existence of the perfect Qur?anic educational system has prompted him to endeavour to describe prescriptions of the Qur?anic verses, so those became as educational perspectives or viewpoints, either with nuance of clarifying, comparing or perfecting, that contain fully messages of moral, religious preaching, and movement, in order to revive the glory of Islam.